Heightened amygdala responsiveness in s‐carriers of 5‐HTTLPR genetic polymorphism reflects enhanced cortical rather than subcortical inputs: An MEG study. Issue 9 (5th June 2017) - Luo, Qian; Holroyd, Tom; Mitchell, Derek; Yu, Henry; Cheng, Xi; Hodgkinson, Colin; Chen, Gang; McCaffrey, Daniel; Goldman, David; Blair, R. James
Abstract: Short allele carriers (S‐carriers) of the serotonin transporter gene (5‐HTTLPR) show an elevated amygdala response to emotional stimuli relative to long allele carriers (LL‐homozygous). However, whether this reflects increased responsiveness of the amygdala generally or interactions between the amygdala and the specific input systems remains unknown. It is argued that the amygdala receives input via a quick subcortical and a slower cortical pathway. If the elevated amygdala response in S‐carriers reflects generally increased amygdala responding, then group differences in amygdala should be seen across the amygdala response time course. However, if the difference is a secondary consequence of enhanced amygdala–cortical interactions, then group differences might only be present later in the amygdala response. Using magnetoencephalography (MEG), we found an enhanced amygdala response to fearful expressions starting 40–50 ms poststimulus. However, group differences in the amygdala were only seen 190–200 ms poststimulus, preceded by increased superior temporal sulcus (STS) responses in S‐carriers from 130 to 140 ms poststimulus. An enhanced amygdala response to angry expressions started 260–270 ms poststimulus with group differences in the amygdala starting at 160–170 ms poststimulus onset, preceded by increased STS responses in S‐carriers from 150 to 160 ms poststimulus. These suggest that enhanced amygdala responses in S‐carriers might reflect enhanced STS‐amygdala connectivity in S‐carriers. Hum Brain Mapp 38:4313–4321, 2017 . ©2017 Wiley Periodicals, Inc.